Cuba : Religion, Social Capital, and Development - Hearn, Adrian H., 1975- (Book collections on Project MUSE., 2008)
Argues that grassroots cultural actors and religious organizations have come to play an important role in social development in Cuba since the early 1990s, and that this process occurred with the active support, and regulation of the state, despite the st.